Evaluation of economic advantage for produced electrical energy usage by solar cell in compression with steam power plant in home in Isfahan city - Abounoori, Abbas Ali; Javadi, Shahram; Ahmadi, Hassan; Gashti, Hadi Parhizi (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The aim of this article is evaluation of economic advantage from using of solar energy (photovoltaic system) in compression with steam power plant in order to supply the electricity of Isfahanâ€™s household (2009 to 2011). For this reason, meanwhile the calculation of used electricity for each house in Isfahan city, the production cost for one kilo watt hour of electricity through two methods of steam power plant and photovoltaic system is estimated from the scale of equationâ€™s uniform annual cost. The result shows that application of photovoltaic system is inadvisable in Isfahan in now condition. It is considerable that due to increasing of electricity requirements and the limitation of fossil sources and the high pollution because of these sources, the usageÂ of resulted energy from steam power plant hasnâ€™t economic justify in the not too distant future.